The long and short of it: The post-crisis corporate CDS market - Nina Boyarchenko; Anna M. Costello; Or Shachar (Federal Reserve Bank of New York, 2019)
The 2007-09 financial crisis highlighted the vulnerability of financial institutions linked by a complex web of credit default swap (CDS) contracts, sparking a wave of regulatory changes to the structure of the market. In this paper, we provide broad evidence on the evolution of the CDS market in the post-crisis period, document the properties of participants' exposures to corporate CDS over time, and study the differential pricing of transactions between different types of counterparties.
Keywords: G10; G12; G19; 330; CDS positions; CDS transactions; dealer market power